Advancing Education Through Extended Reality and Internet of Everything Enabled Metaverses: Applications, Challenges, and Open Issues - Senthil Kumar Jagatheesaperumal (19256551) (2024)
Metaverse has evolved as one of the popular research agenda that let users learn, socialize, and collaborate in a networked 3-D immersive virtual world. Due to the rich multimedia streaming capability and immersive user experience with high-speed communication, the metaverse is an ideal model for education, training, and skill development tasks. To facilitate research in this area, we provide a comprehensive review of the various educational use cases and explore how enabling technologies, such as extended reality and the Internet of Everything will play a major role in educational services in future metaverses. Then, we provide an overview of metaverse-based educational applications focusing on education, training, and skill development and analyze the technologies they are built upon. We identify common research problems and future research directions in the domain. This article also identifies core ethical considerations of metaverse for education and potential pitfalls. We believe this survey can fully demonstrate the versatility of metaverse-driven education, which could serve as a potential guideline for the researchers. Other Information Published in: IEEE Transactions on Learning Technologies License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1109/tlt.2024.3358859